Prevalence of distress and association with psychological factors among healthcare workers in a non covid-19 hospital in Kota Kinabalu, Sabah - Ag Azmi Ag Damit (2022)
The Covid-19 pandemic has caused much psychological distress amongst healthcare workers, more those serving in Covid-19 hospitals. This can lead to high levels of burnout, due to increasingly challenging working environments. The factors underlying depression and anxiety, chiefly psychological process variables (mindfulness and psychological flexibility) should be examined to ascertain particular targets of treatment. At the same time, fear of Covid-19 and stress of Covid-19 have emerged, suggesting that the stressors of this pandemic are very divergent from previously. A cross-sectional study was performed amongst 210 healthcare workers in Queen Elizabeth 2 Hospital Kota Kinabalu, Sabah. Questionnaires pertaining to the following variables were administered: sociodemographic variables (age, gender and living status); burnout; psychological process variables; fear of Covid-19; stress of Covid-19; depression, anxiety, and stress. Bivariate correlations were assessed amongst all continuous variables and hierarchical multiple regressions were performed using depression and anxiety as separate dependent variables. At the first stage, sociodemographic variables were inputted; burnout, coping styles, and psychological process variables at the second stage; then at the third stage, the fear and stress of Covid-19 and the burnout variables were inputted. Age, psychological flexibility, and dysfunctional coping styles emerged as consistent predictor variables for both depression and anxiety. Mindfulness emerged as an additional predictor variable for depression but not anxiety. This study demonstrates that brief interventions that target psychological flexibility will decrease experiential avoidance. This suggests that depression and anxiety in healthcare workers undergoing high levels of stress can be diminished by appropriate interventions that target relevant psychological constructs.